Solidarity digital map: Innovation opportunities for social mobilization in times of pandemic caused by COVID19 (Orinoquia, 2021)
The pandemic caused by COVID-19 impacted the lives of all communities, making it necessary to creatively address the challenges it produced. In that regard, it motivated the generation of innovative solutions in the development of internship programs for health sciences courses that facilitate the students’ interaction with social reality from the approach of social determinants of health. In the same way, the state of economic, social and ecological emergency mobilized communities and social leaders to generate participatory solutions to the problems that can seriously impact vulnerable populationssuch as access to health services, impact on life modes, and other conditions of insecurity and uncertainty caused or aggravated by emergency states. It is at this point where a community experience is born between the ECCI University and the “Frenalacurva” initiative (present in 16 countries), in coordination with Kitum.org (which encourages the use of technology in citizen participation for disaster risk management). At “FrenaLaCurva”, communities have organized to support COVID-19 response efforts, including digital mapping of people and communities in need, as well as offering solidarity solutions to address those needs. The community experience took place during April, May, and June 2020 in the 32 departments of Colombia aligning with the work of the 6 allied countries of “FrenaLaCurva”. The conclusion of this community experience allowed the students of the nursing program to develop an interprofessional, interdisciplinary and intersectoral work through the georeferencing of 361 identification reports and the geolocation of needs and offers of help open by social networks in the 32 departments of the country. In addition to the development of activities in health education, the participation of the allied 16 countries of “FrenaLaCurva” in actions of teleconsultation and tele-orientation for individuals, families or communities on mental health and the elderly, children and adolescents in sexual and reproductive health, benefited more than 276 synchronous users and 619 asynchronous views. The identified challenges consisted mostly in the lack of knowledge in the use of georeferencing technology aimed at strengthening actions in public health, a deficient access to systematically updated databases and the absence of governmental entities’ support to facilitate the sustainability of the platform.
Keywords: Community Health Nursing; Organizational Innovation; Telemedicine; Digital Inclusion; Public Health